Developing a Computer Program for Mathematical Investigation of Stepped Planing Hull Characteristics - Loni, Afshin; Ghadimi, Parviz; Nowruzi, Hashem; Dashtimanesh, Abbas (International Journal of Physical Research, 2013)
Few authors have investigated the behavior of stepped planing hulls, so far. However, effects of such hulls on planing craft performance indicate that it can be a great improvement and must be analyzed more precisely. For this purpose, a mathematical model which was previously developed based on Savitsky’s formulation is implemented and the performance of a specific stepped planing hull is studied. Furthermore, a computer program is developed and effects of various parameters on stepped planing hull performance are investigated. Based on the obtained results, it is concluded that different heights of step leads to large variation of required power for the planing hull. Moreover, it can be mentioned that the parametric studies which are conducted in this article can be a good guide for engineering at initial design of a stepped planing hull.